Antibiotic selection and risk profiles in patients receiving antibacterial cardiovascular implantable electronic device envelopes – a real world sample and analysis. (14th October 2021) - Deering, T
Abstract: Background: The use of a cardiovascular implantable electronic device (CIED) envelope impregnated with antibiotics provides short-term local antibiotic delivery in the implant pocket and may lower infection risk. Biologic antibacterial (BIO) envelopes, such as the porcine extracellular matrix (ECM) device hydrated with antibiotics, facilitate active remodeling of the pocket into vital, vascularized tissue and provide short-term local antibiotic delivery. Limited clinical data is available on real-world clinician patient selection criteria, antibiotic choices, or clinical outcomes. Purpose: To explore antibiotic hydration solution physician choices with respect to patient profiles, and to determine post-implant infection outcomes in patients receiving a CIED BIO envelope. Methods: A post-hoc sub-analysis of a multicenter, non-randomized study of 1017 patients receiving a biologic envelope (hydrated with or without antibiotics) during CIED procedures (SECURE Study) assessed antibiotic hydration choices, patient risk profiles, and the type and timing of infection for days 0–90 post procedure. Patient selection and antibiotic hydration choice were at the discretion of the treating physician. Results: 850 patients received BIO envelopes, with a mean age of 71.9 years, and 60.5% having ≥2 standard infection risk factors. High power devices accounted for 47.6% and reoperations for 44.0% of the procedures. Antibiotic choice for envelope hydration prior to implantation is described in Table 1 below. Also, antibiotic combinations with gentamicin were used in 18.1% and other antibiotic combinations in 9.2% of patients. Patients receiving gentamicin hydrated BIO envelopes (BIO+G) trended toward fewer pocket infections vs. those without gentamicin (BIO-G) (0.0% vs. 1.6%, p=0.070) but the overall pocket infection rate of 1.2% was not significantly different based upon antibiotic choice. In a multivariate logistic regression model designed to predict the total infection rate, the use of gentamicin was associated with a 3-fold reduction in likelihood of infection, OR 3.0 (1.0–10.0); AUC=0.70. No differences in overall infection rates among patients undergoing lead or pocket revision only procedures (0.0% vs. 0.0%) or other major adverse events were observed based upon antibiotic usage. Conclusions: Real world clinical decision-making regarding antibiotic choice for biologic antibacterial envelopes varies among implanting clinicians and influences observed outcomes. The use of biologic antibacterial envelopes hydrated with gentamicin was associated with a lower likelihood of infection within 90 days when compared to biologic envelopes hydrated without gentamicin. Clinical trials to optimize patient selection processes and determine the best antibiotic choice when employing a CIED envelope merit further investigation. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The work was supported by Aziyo Biologics, Inc.